PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN (STUDI PADA PELANGGAN MEDIN BEAUTY) - PUTRI YOHANA, GISSELA (Jurnal Ilmu Manajemen (JIM), 2017)
The development of service businesses and the ever-increasing number of human populations and an increasingly diverse lifestyle make the level of human need for appearance, beauty, and fitness also growing. Lifestyle business, particularly in the areas of appearance, beauty, and fitness as beauty and body-care clinics currently showing good growth. Customer interest in beauty clinic is very popular today because customers can consult directly with skin care experts. This study aims to analyze and discuss the effect of service quality and price on customer satisfaction and loyalty. The sampling technique used is non-probability sampling and sampling methods done by sampling incidental taken as many as 220 people. The population is customers aged 20 to 30 years who have used the services of Medin Beauty Pandaan. Scale of measurement in this study using Likert scale. The measuring instrument used is a questionnaire. The analysis tool using path analysis by AMOS program. The results showed that the quality of service Medin Beauty Pandaan has a positive influence on satisfaction. Price has a positive effect on satisfaction. Satisfaction has a positive effect on loyalty. In this study, the relationship of each variable is positive so that mediation is proven partially. Keywords: service quality, price, satisfaction, loyalty